The matched-filter bound on optimal space-time processing in correlated fading channels. - Roy, S.
This paper presents a theoretical analysis of the matched-filter bound on N-branch space-time processing receivers in a frequency-selective correlated fading environment. The development is based on a Karhunen-Loe`ve expansion in the frequency domain. Although many other works are based on similar expansions, we present a more general analytical framework in the frequency domain covering Rayleigh and Rician fading scenarios, with and without branch correlations and/or unequal branch powers. The Rician fading scenario is approximated using a Nakagami-m distribution. The branch correlations and unequal branch powers are dealt with through a simple and novel device, the concatenated array-equivalent channel. Likewise, a novel approach is presented that reduces the Rician fading case to an equivalent Rayleigh-fading system. Furthermore, results are presented for different array topologies where correlation characteristics are obtained with the help of a measurement-validated correlation model situated in the local multipoint distribution service band, i.e., the carrier frequency used in the measurements was 29.5 GHz.
Keywords: 29.5 GHz; Karhunen-Loeve expansion; Rayleigh fading channel; Rician fading channel; Array signal processing; Broadband communication; Concatenated array-equivalent channel; Correlated fading channel; Matched-filter bound; Maximum-likelihood sequence estimation; Space-time processing